Problem-based medical education in general practice: experience from Linköping, Sweden. - Foldevi, M; Sommansson, G; Trell, E (British Journal of General Practice, 1994)
Medical services which are better suited to the needs of the community are increasingly demanded, for example by national governments, and depend to a great extent on education of the new generations of doctors. Problem-based learning in general practice at the community level represents a method of providing appropriate education. This paper describes some of the experiences of undergraduate and continuing medical education at the Faculty of Health Sciences, Linköping University, Sweden, which since 1986 have been entirely problem-based. General practice forms the backbone of the curriculum and is its largest subject. Problem-based learning in general practice and quality assurance have much in common. This applies over the spectrum of lifelong education, from the undergraduate curriculum through vocational training to later stages of continuing medical education. Involvement and understanding, a feeling of purpose, sharing and cooperation and a wish for self-improvement are all stimulated by the problem-based method. This approach has helped in the creation of a curriculum with general practice as the largest contributor, with early contact with patients in the community, and with ordinary general practitioners as teachers, tutors and examiners in spite of a relatively poorly developed primary care organization.